2002
DOI: 10.2166/wst.2002.0461
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and physiological characterization of a “Nostocoida limicola”-like organism isolated from activated sludge

Abstract: Ten strains of "Nostocoida limicola"-like organisms were isolated from a municipal wastewater treatment plant with minor industrial effluent. The near complete 16S rDNA sequences were determined for four strains to analyze the position of the organisms within the phylogenetic tree. All four isolates showed the same 16S rRNA sequence and cluster within the green non sulfur bacteria. Hybridization with oligonucleotide probe AHW183 designed complementarily to diagnostic regions of the 16S rRNA sequences showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…Thus, the isolated strains look like the Gram-variable filamentous bacteria in activated sludge with the 'Nostocoida limicola' type II morphology described by Eikelboom & van Buijsen (1983). This morphotype was also observed in previous studies (Snaidr et al, 2002;Schade et al, 2002;Blackall et al, 2000;Levantesi et al, 2004). Our results confirm the observation that different filaments from the 'N.…”
supporting
confidence: 93%
“…Thus, the isolated strains look like the Gram-variable filamentous bacteria in activated sludge with the 'Nostocoida limicola' type II morphology described by Eikelboom & van Buijsen (1983). This morphotype was also observed in previous studies (Snaidr et al, 2002;Schade et al, 2002;Blackall et al, 2000;Levantesi et al, 2004). Our results confirm the observation that different filaments from the 'N.…”
supporting
confidence: 93%
“…In some recent cases with bulking incidents with both municipal and industrial wastewaters, we have observed that morphotypes 0803 in fact belong to the phylum Chloroflexi, as they were targeted by the phylum probes. These findings suggest that this morphotype either was misidentified in the study by Bradford et al (1996) or type 0803 is not a single genetic entity, as has also been observed for other morphotypes such as type 1863 (Rossetti et al, 1997;Seviour et al, 1997) and Nostocoida limicola (Liu et al, 2000(Liu et al, , 2001Schade et al, 2002;Levantesi et al, 2004).…”
Section: Introductionsupporting
confidence: 61%
“…A similar observation was made with N. limicola II, in which filaments unambiguously identified microscopically as this morphotype responded not only to the NLIMII and HGC 69a probes, as expected from the sequence data from cultured isolates of this bacterium , but also to the ALF 1b and ALF 968 probes for the a-Proteobacteria (Fig. N. limicola II filaments belonging to both the a-Proteobacteria (Snaidr et al, 2001) and the Chloroflexus group (Schade et al, 2001) have recently been described based on other cultured isolates, illustrating how phylogenetically diverse this morphotype is, and 16S rRNA targeted FISH probes are available for their in situ identification in activated sludge plants. In fact the a-Proteobacterial N. limicola II were often the dominant filament in some biomass samples examined, and both phylogenetic types were frequently seen (Table 2) in biomass samples from a single plant.…”
Section: Discussionsupporting
confidence: 80%